2012
DOI: 10.1124/mol.112.080903
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Trimeric P2X2 Receptors by Fewer than Three ATP Molecules

Abstract: P2X receptors are trimeric membrane proteins. When they bind extracellular ATP, a conformational change occurs that opens a transmembrane ion channel. The ATP-binding pocket is formed in a cleft between two subunits, and a critical amino acid residue for ATP contact is Lys 69 (P2X2 numbering). In the present work, we sought to determine whether the binding of fewer than three ATP molecules could open the ion channel. We expressed eight concatenated cDNAs in human embryonic kidney cells, which encoded three ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 25 publications
(40 reference statements)
7
36
0
Order By: Relevance
“…P329 is oriented toward other P329 residues in adjacent subunits and is solvent-exposed. We found that bridging two of the three cysteines was sufficient to open and close trimeric P2X2 receptors, consistent with the finding that only two intact agonist-binding sites (and by inference only two ATP molecules) are required for P2X receptor activation (26). It is noteworthy that at rest (the closed channel state) the BMA was in its higher-energy cis isomer, suggesting it is constrained in this form by the protein to which it is conjugated.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…P329 is oriented toward other P329 residues in adjacent subunits and is solvent-exposed. We found that bridging two of the three cysteines was sufficient to open and close trimeric P2X2 receptors, consistent with the finding that only two intact agonist-binding sites (and by inference only two ATP molecules) are required for P2X receptor activation (26). It is noteworthy that at rest (the closed channel state) the BMA was in its higher-energy cis isomer, suggesting it is constrained in this form by the protein to which it is conjugated.…”
Section: Discussionsupporting
confidence: 86%
“…Two of the three forms with a single P329C substitution also gave small responses to light. This was most notable for the form with cysteine in the first of the three concatenated subunits and may reflect aberrant ("heads-up") channel formation from three N-terminal subunits or from minimal breakdown of the concatemers as observed and discussed previously (26).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…(1) The binding sites of ATP are contributed by domains from different subunits, namely, the head and LF domains from the same subunit, and the DF and upper body domains from a neighbor subunit ( Figure 4A). Therefore, there are three ATP binding sites in a three-fold symmetric mode, although a recent study showed that ATP binding at only two of the three sites is sufficient for channel opening [107] . (2) The body domains of the three subunits intertwine with each other, forming the fundamental core of the P2X receptors ( Figure 4B), which is surrounded by the three ATP binding sites.…”
Section: Domain-domain Interactions and Coordinated Motions Of Multi-mentioning
confidence: 99%
“…Several lines of evidence indicated that the functional protein was a trimer: indeed, three ATP-binding sites had been suggested by Bean [14] on the basis of his ATP dose-response curves from bullfrog sensory neurons. This evidence included biochemical approaches using blue native polyacrylamide gel electrophoresis [30] and functional approaches with co-expression and concatenation of subunits carrying reporter mutations [31][32][33][34][35]. The demonstration that P2X receptors were trimers set them in clear distinction from the tetrameric glutamate-gated ion channels and the pentameric nicotinic superfamily (which also includes channels gated by glycine, g-aminobutryic acid and 5-hydroxytryptamine; [22]).…”
Section: Following Cdna Cloningmentioning
confidence: 99%